2022
DOI: 10.1155/2022/6101800
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Histological, and Physiological Responses of Female Orange Mud Crab, Scylla olivacea (Herbst, 1796), Fed with Different Dietary Lipid Levels

Abstract: The main focus of the study was to assess the effect of lipid levels on the reproduction of the female orange mud crab, Scylla olivacea. Four isonitrogenous feed (~420 g/kg) were formulated with different lipid percentages: T 1 = 60   g / kg , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…The present research is the first to study the effect of dietary lipid levels on gonad development of O. macrolepis broodstock. The current results showed that no significant differences were noted in the histological features of ovary sectioning in O. macrolepis broodstock among five dietary groups; a similar result was found in orange mud crabs' ovaries [57]. While in Chinese sturgeon, higher dietary lipid levels improved ovarian development, with a higher percent of mature oocytes and larger giant oocyte (diameter), especially for the 24-month feeding period [58].…”
Section: Effect Of Lipid Level On Gonad Development Of O Macrolepis B...supporting
confidence: 65%
“…The present research is the first to study the effect of dietary lipid levels on gonad development of O. macrolepis broodstock. The current results showed that no significant differences were noted in the histological features of ovary sectioning in O. macrolepis broodstock among five dietary groups; a similar result was found in orange mud crabs' ovaries [57]. While in Chinese sturgeon, higher dietary lipid levels improved ovarian development, with a higher percent of mature oocytes and larger giant oocyte (diameter), especially for the 24-month feeding period [58].…”
Section: Effect Of Lipid Level On Gonad Development Of O Macrolepis B...supporting
confidence: 65%
“…Similarly, in this study, we also found that long-term feeding of a diet with 0.27% cholesterol can significantly improve the BW, HSI, and GSI of Eriocheir sinensis. BW, HSI, and GSI are three important indexes in the process of broodstock breeding, which can directly determine the reproductive performance [10,31]. In addition, cholesterol has no significant effect on the CF and MY of crabs, but the SR of cholesterol deficiency group is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The broodstock nutrition of shrimp and crab has always been a weak point in the study of aquatic nutrition. Currently, research on the nutrition of shrimp and crab is mostly focused on the juvenile stage [10][11][12][13][14]. However, shrimps and crabs have different nutrient requirements at different growth stages, especially during the ovarian development stage, the broodstock needs to accumulate a large amount of nutrients to meet the requirements of ovarian development [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The histological study was done based on the standard histological procedure previously done by Aaqillah-Amr et al (2022). Meanwhile, fatty acid analyses were carried out in both ovary and hepatopancreas following the one-step method analysis by Abdulkadir and Tsuchiya (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the morphological analysis of the ovary was based on the measurement of the gonadosomatic index (GSI) following de Vlaming et al (1982). All calculations were as followed:left)(i2ptBody weight gain0.25em)(BWG,%goodbreak=finalBWinitialBWinitial0.25emBWgoodbreak×100%left)(ii2ptCarapace width gain0.25em)(CWG,%goodbreak=final0.25emCWinitial0.25emCWinitial0.25emCWgoodbreak×100%left0.25em)(iii2ptGonadosomatic index,GSI0.25em)(%goodbreak=Ovary weightBody weightgoodbreak×100%The histological study was done based on the standard histological procedure previously done by Aaqillah‐Amr et al (2022). Meanwhile, fatty acid analyses were carried out in both ovary and hepatopancreas following the one‐step method analysis by Abdulkadir and Tsuchiya (2008).…”
Section: Introductionmentioning
confidence: 99%